Hospital-acquired pneumonia among pediatric trauma patients treated at national trauma centers. Issue 6 (June 2015) - Ortega, Henry W.; Cutler, Gretchen; Dreyfus, Jill; Flood, Andrew; Kharbanda, Anupam
Abstract : BACKGROUND: Injury is the leading cause of hospitalization in children, and as many as 5% of hospitalized injured children require mechanical ventilation. Despite this, little is known about the complications associated with mechanical ventilation, including pneumonia. METHODS: This is a retrospective analysis of trauma patients younger than 19 years from the National Trauma Data Bank from 2009 to 2011. Descriptive statistics were used to examine the patient population. Baseline characteristics were compared between subgroups using t tests and χ 2 tests. Generalized linear models were used to identify risk factors for hospital-acquired pneumonia adjusting for clustering of patients by hospital. RESULTS: A total of 252, 187 patients were eligible for analysis, and 1, 915 patients were diagnosed with pneumonia. Most patients were male (66.3%), were white (54.2%), had no comorbidities (88.9%), and were not considered severely injured (85.5% with an Injury Severity Score [ISS] < 16). The mean (SD) length of stay was 2.9 (5.2) days. Patients who developed pneumonia were older (16–18 years, 61.7% vs. 31.1%, p < 0.0001), had an increased length of stay (20.9 days vs. 2.8 days, p < 0.0001), more intensive care days (13.9 days vs. 0.7 days, p < 0.0001), and more ventilation days (9.5 days vs. 0.3 days, p < 0.0001) compared with those who did not develop pneumonia. The rate of pneumonia nearly doubled in patients spending 2 days on a ventilator (odds ratio [OR], 5.52; 95% confidence interval [CI], 3.45–8.84), doubled again for patients spending 3 days (OR, 10.59; 95% CI, 6.38–17.61), and doubled again for patients spending 5 days (OR, 23.72; 95% CI, 13.36–42.15) mechanically ventilated. The presence of two comorbid conditions was associated with twice the odds of developing pneumonia (OR, 2.10; 95% CI, 1.47–1.78). CONCLUSION: Prolonged mechanical ventilation, increased injury severity, older age, and presence of multiple comorbid conditions all increase the risk of pneumonia in injured children. Preventive measures should be aggressively used in injured children at high risk for the development of pneumonia. LEVEL OF EVIDENCE: Epidemiologic study, level III.